Monetary Policy, Financial Constraints, and Redistribution - Christian Loenser; Andreas Schabert (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
This paper examines how financial constraints affect redistribution via monetary policy. We explore a novel mechanism of monetary non-neutrality, which is based on debt limits imposed in nominal terms. Specifically, when debt is constrained by current income, monetary policy can alter the real terms of borrowing. Changes in inflation exert ambiguous effects, depending on the initial debt/wealth position and the willingness to borrow. We show analytically that borrowers can benefit from increased debt limits under lower inflation rates. This novel effect can dominate conventional debt deflation effects. We find that particularly less indebted borrowers as well as potential future borrowers gain and that aggregate welfare can be enhanced under a permanent reduction in inflation.
Keywords: D52; E44; E52; 330; Monetary policy; redistribution; borrowing limits; non-state contingent nominal debt; heterogeneous agents